Perbaikan Proses Dandori di PT. Astra Otoparts Tbk. Divisi Adiwira Plastik - Gani, Albert Junaedi; Bendatu, Liem Yenny (Jurnal Titra, 2015)
This paper discusses the abnormality in dandori process and improvements to overcome it. Dandori is a process of changing mold or material during the production. Lately, dandori process at PT. Astra Otoparts Tbk. still experienced abnormality such as material unreadiness, lack of facilities and infrastructure, and long barrel washing process. This research aims to reduce the preparation time and processing time of dandori and line stop. Quality control circle was used as the main method to design the improvements. Improvements are supported by some work standardizations for maintaining continuous improvements. The implementation of the improvements result in reducing dandori total time by 23 hours per month or 10,7% and average dandori time per process is reduced by 6,9 minutes or 17,6%. Material heating line stop reduced by an average of 15,5 hours per month or 35,8%.